Efficacy and mechanism of intermittent fasting in metabolic associated fatty liver disease based on ultraperformance liquid chromatography-tandem mass spectrometry - Deng, Jiang; Feng, Dandan; Jia, Xiaoli; Zhai, Song; Liu, Yixin; Gao, Ning; Zhang, Xin; Li, Mei; Lu, Mengnan; Liu, Chenrui; Dang, Shuangsuo; Shi, Juanjuan (Frontiers in Nutrition, 2022)
Objectives: Metabolic associated fatty liver disease (MAFLD) lacks specific drug therapy. This study aimed to analyze the efficacy and mechanism of intermittent fasting combined with lipidomics. Methods: Thirty-two male rats were randomly divided into three groups: Normal group, given a standard diet; MAFLD group, a 60% high-fat diet; and time-restricted fasting (TRF)group, a 60% high-fat diet, and eating was allowed for 6 h per day(16:00 to 22:00). After 15 weeks, liver lipidomics and other indicators were compared. Results: A total of 1062 metabolites were detected. Compared with the Normal group, weight, body fat ratio, aspartate aminotransferase, total cholesterol, low-density cholesterol, fasting blood glucose, uric acid, and levels of 317 lipids including triglycerides (TG) (17:0-18:1-20:4)were higher, whereas levels of 265 lipids including phosphatidyl ethanolamine(PE) (17:0-20:5)were downregulated in the MAFLD group (P<0.05). Compared with the MAFLD group, weight, body fat ratio, daily food intake, and levels of 253 lipids including TG(17:0-18:1-22:5)were lower than the TRF group. Furthermore, the levels of 82 lipids including phosphatidylcholine(PC) (20:4_22:6) were upregulated (P<0.05), and serum TG level was increased in the TRF group; however, the difference was not statistically significant(P>0.05). Enrichment analysis of differential metabolites showed that the pathways involved mainly included metabolic pathways, regulation of lipolysis in adipocytes, fat digestion and absorption. Reverse-transcription polymerase chain reaction proved that time-restricted fasting improved the abnormal expression of FAS and PPARα genes in the MAFLD group (P<0.05). Conclusions: Six hours of TRF improved MAFLD by reducing food intake by 13% and improve the PPARα/FAS pathway, which is a simple and effective measure for the prevention and treatment of MAFLD.